Atomic ordering and magnetic properties of quaternary Heusler alloys NiCuMnZ (Z=In, Sn, Sb). (July 2017) - Ma, Yuexing; Hao, Hongyue; Xin, Yuepeng; Luo, Hongzhi; Liu, Heyan; Meng, Fanbin; Liu, Enke
Abstract: A series of quaternary Heusler alloys NiCuMnZ (Z = In, Sn, Sb) have been prepared experimentally. Their structural and magnetic properties have been investigated by XRD, magnetic measurements and first-principles calculations. NiCuMnZ all crystallize in a cubic Heusler structure. But the atomic ordering in them is different and related to the main group element Z. NiCuMnSb is highly ordered while NiCuMnIn and NiCuMnSn have a degree of Cu-Mn disorder in the lattice. In these alloys, Cu atom has strong preference for the B (0.25, 0.25, 0.25) site, though Cu has more valence electrons than Mn and Ni. The saturation magnetization Ms at 5 K is 3.99μB /f.u., 4.20μB /f.u. and 4.02μB /f.u. for NiCuMnSb, NiCuMnSn and NiCuMnIn, respectively. First-principles calculations suggest that the large total moments mainly come from the contribution of Mn. The TC decreases rapidly from 716 K in NiCuMnSb to 340 K in NiCuMnIn, relating to the increasing degree of atomic disorder in their lattice. But the partial moments of Mn are always in ferromagnetic coupling though they are nearest neighbors in partly disordered NiCuMnSn and NiCuMnIn. Highlights: Heusler alloys NiCuMnIn and NiCuMnSn were synthesized successfully. Cu has strong preference for B site despite the "valence electrons rule". Atomic ordering in NiCuMnZ is related to the main group element Z. Ferromagnetic coupling observed between nearest neighbor Mn in disorder NiCuMnIn.